Kondisi Keuangan, Opinion Shopping dan Opini Audit Going Concern pada Perusahaan Pertambangan yang Terdaftar di BEI - Bahtiar Effendi (Universitas Matana, 2019)
Going concern audit opinion is the auditor's opinion to ascertain whether the company can maintain the survival of the entity. The importance of disclosing the company's survival will have an impact on steakholder valuation and trust. The purpose of this study was to determine the effect of financial conditions, opinion shopping and disclosure on going concern audit opinions on mining companies listed on the Indonesia Stock Exchange (IDX) during the period between 2014-2017.The population in this study are mining companies listed on the Indonesia Stock Exchange in the 2014-2017 period. The company becomes a sample based on the purposive sampling method chosen by certain criteria. The type of data used in this study is secondary data. Data analysis using multiple linear regression methods using SPSS 24 as an analysis tool.The results of the study show that Opinion shopping has a negative effect on the going concern audit opinion while disclosure has a positive effect on the going concern audit opinion.